Jahresbericht des Vereins Kunsthalle Bern 1991 / 92. - Hahnloser, Bernhard; Kunsthalle Bern (Bern : Kunsthalle Bern, 1992)
Iglesias, Cristina ; De Keyser, Raoul ; Wool, Christopher ; Brandl, Herbert ; Davey, Grenville ; Opie, Julian ; Lichtsteiner, Alois ; etc.
Duits
boek